Rejection of Technoculture in The Avenger: Infinity War Movie by Anthony and Joe Russo: An Application of Jean Francois Lyotard’s Postmodern Theory - Andhika Putri Ningsih; La Aso (Program Studi Sastra Inggris Fakultas Ilmu Budaya Universitas Halu Oleo, 2019)
This research is intended to analyze the technoculture work and rejected in the Avengers: Infinity War using Jean Francois Lyotard postmodern theory. The source of data in this study is the Avengers: Infinity War movie by Anthony and Joe Russo that is published in 2018. The data was collected from watches the movie several times, collecting the dialog, and screenshotting the image that related to the issue. The postmodern theory of Jean Francois Lyotard is used as a tool for analyzing the finding of technoculture in the Avengers: Infinity War. The result of this study shows that: (1) technoculture are represented through the power of technology and science such as Captain America, Spiderman, Iron Man, and Hulk, Individualism is one of the characteristics of a modernist society. Individualism is displayed through Iron Man and Thor that think they can solve their own problems. Rationality is the quality or state of being rational based on agreeable to reason.